A cortico-collicular pathway for motor planning in a memory-dependent perceptual decision task - Chunyu A. Duan (Nature Portfolio, 2021)
Duan, Pan et al. find that the premotor cortex cooperates with the midbrain superior colliculus via direct projections to implement decision maintenance. These results reveal mechanisms of cortico-collicular interaction during cognition and action in a pathway- and cell-type-specific manner.